The general expression for the quadratic function is :
![f(x)=a(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/high-school/lv6wh92oxxg1yzd73cyhfmkxhau9bpvca1.png)
where, Vertex : (h, k) and h = -b/2a and k = f(h)
In the given question the vertex is ( -1, 3)
Substitute the value of the h = -1 and k = 3
Thus :
![\begin{gathered} f(x)=a(x-h)^2+k \\ f(x)=a(x-(-1))^2+3 \\ f(x)=a(x+1)^2+3 \\ as\text{ the curve passed through : (2, 4) } \\ substitute\text{ x = 2 and at f(2) = 4} \\ f(2)=a(2+1)^2+3 \\ 4=a(3)^2+3 \\ 4=9a+3 \\ 9a=4-3 \\ 9a=1 \\ a=(1)/(9) \\ \text{Substitute the value in the expression :} \\ f(x)=(1)/(9)(x+1)^2+3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/owo533i9252kth8epl4sbva1c7cl51zep2.png)
The expression for the quadratic expression is :
f(x) = 1/9(x + 1)² + 3
Answer : f(x) = 1/9(x + 1)² + 3